The efficacy of a discontinuous graded exercise test in measuring peak oxygen uptake in children aged 8 to 10 years - Lambrick, D.; Jakeman, J.; Grigg, R.; Kaufmann, S.; Faulkner, J. (Biology of Sport, 2017)
As children's natural activity patterns are highly intermittent in nature, and characterised by rapid changes from rest to vigorous physical activity, discontinuous exercise tests may be considered ecologically valid for this population group. This study compared the peak physiological responses from a discontinuous and continuous graded exercise test (GXT_D, GXT_C, respectively) during treadmill exercise in children. Twenty-one healthy children (9.6 ± 0.6 y) completed GXT_D and GXT_C in a randomised order, separated by 72-hours. Following each GXT, and after a 15-minute recovery, participants completed a verification test at 105% of the velocity attained at peak oxygen consumption (VO 2 peak). There were no differences in VO 2 peak (55.3 ± 8.2 cf. 54.4 ± 7.6 mLkg-1min-1) or maximal heart rate (202 ± 10 cf. 204 ± 8 bmin-1) between GXT_C and GXT_D, respectively (P>.05). Peak running speed (10.7 ± 0.9 cf. 12.1 ± 1.3 kmh-1) and respiratory exchange ratio (1.04 ± 0.05 cf. 0.92 ± 0.05) were however different between tests (P .05), VO 2 peak (53.3 ± 7.3 mLkg-1min-1) and heart rate (197 ± 13 bmin-1) were significantly lower in the GXT_D verification test (P<.05). In conclusion, a discontinuous GXT is an accurate measure of VO 2 peak in children aged 8 to 10 years and may be a valid alternative to a continuous GXT, despite its longer duration.